Structural characteristics, antioxidant and hypoglycemic activities of polysaccharides from Mori Fructus based on different extraction methods - Huang, Yuanyuan; Xie, Wen; Tang, Ting; Chen, Huaguo; Zhou, Xin (Frontiers in Nutrition, 2023)
The mulberry (Mori Fructus), which is rich in many nutrients needed by the human body, serves as both food and medicine. Polysaccharides, which are considered to be important pharmacological components of mulberry, have received a lot of study for their structure and biological activity. In this study, six mulberry fruit polysaccharides (MFPs) were extracted by different extraction methods, and their physicochemical structures, antioxidant, and hypoglycemic biological activities were investigated and compared. According to the findings, MFP-III exhibited the best α-glucosidase and α-amylase inhibition, whereas MFP-IV had the strongest scavenging activity against DPPH and ABTS. Scanner electron microscopy (SEM) and high-performance liquid chromatography (HPLC) analysis showed that the apparent morphology and monosaccharide content of MFP were significantly impacted by the different extraction techniques. The results of experiments using Congo red, Fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR), thermogravimetric analysis (TG), and the Congo red experiment showed that the MFP functional groups, glycosidic bonds, triple helix structure, and thermal stability were not significantly different between the extraction methods. According to the aforementioned research, various extraction methods had different effects on the chemical composition and biological activity of mulberry polysaccharides. This information can provide a scientific basis for selecting suitable extraction methods to obtain mulberry polysaccharides with ideal biological activity.